Mycotoxins in adult population from Portugal: Overall results and determinants of exposure - Vidal, Arnau (2020)
Human biomonitoring (HBM) is recognized as an important tool to assess the Human exposure to chemicals, contributing to describe trends and patterns of exposure over time and to identify population groups that could be under risk. Mycotoxins, fungi secondary metabolites that produce toxic effects in humans, are important compounds found in foods usually consumed worldwide in a daily basis. In Portugal, scarce data are available regarding exposure to mycotoxins and the determinants of this exposure. In the scope of the National Food, Nutrition, and Physical Activity Survey of the Portuguese General Population (2015-2016), 24h-urine samples from 94 participants were analyzed by liquid chromatography–mass spectrometry (LC-MS/MS) for the simultaneous determination of 37 urinary mycotoxins’ biomarkers and data obtained used to estimate the probable daily intake as well as the risk characterization applying the Hazard Quotient approach. Participants performed two face-to-face interviews and dietary intake was obtained by two non-consecutive 24-hours recalls with a time interval between 8 and 15 days, complemented with a Food Propensity Questionnaire. Results revealed the exposure of Portuguese population to zearalenone, deoxynivalenol, ochratoxin A, alternariol, citrinin and fumonisin B1 through the quantification in 24h urine and first-morning urine paired samples. Risk characterization data revealed a potential concern to some reported mycotoxins since the reference intake values were exceeded by some of the considered participants. The present study generated, for the first time and within a HBM study, reliable data on internal exposure to mycotoxins at individual level for the Portuguese population. These data were crucial to characterize the determinants of exposure and to support risk managers to establish preventive policy measures that contribute to ensure the public health protection.